2017
DOI: 10.1007/978-3-319-48511-9_24
|View full text |Cite
|
Sign up to set email alerts
|

QR Code and the Wine Sector: What Contents? An Exploratory Research Study on the Wine Industry

Abstract: This paper presents an explorative analysis of the contents shared through QR codes as a tool of proximity marketing. The aim of the research is to identify the most common links shared through the QR code technology, in order to investigate the use of this tool from a marketing point of view. Moreover, the research explores the main aspects of the communications related to the contents shared through QR codes. Specifically, the authors focus on hedonic aspects and functional ones. Finally, the research aims a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Using QR Codes for Food Product Packaging: Balancing Functional and Hedonistic Aspects Most respondents used QR codes on food products to access manufacturing information and stated that the list of ingredients in a nutrition table would be the most useful. However, a survey of QR codes on wine packaging by Acuti et al (2017) revealed that the most effective technical content or data were related to information with hedonistic aspects. Consumers use QR codes to obtain additional information that is usually not included in packaging.…”
Section: Qr Code Scanning: Usage Motivators and Weaknessesmentioning
confidence: 99%
“…Using QR Codes for Food Product Packaging: Balancing Functional and Hedonistic Aspects Most respondents used QR codes on food products to access manufacturing information and stated that the list of ingredients in a nutrition table would be the most useful. However, a survey of QR codes on wine packaging by Acuti et al (2017) revealed that the most effective technical content or data were related to information with hedonistic aspects. Consumers use QR codes to obtain additional information that is usually not included in packaging.…”
Section: Qr Code Scanning: Usage Motivators and Weaknessesmentioning
confidence: 99%